"Każda z nich ma to, czego nie ma druga": konstruowanie kobiecości i męskości w "Sezamie i Liliach" Johna Ruskina - Dobosiewicz, Ilona (Er(r)go. Teoria - Literatura - Kultura, 2006)
Ilona Dobosiewicz, “Each of them has what the other doesn’t:” Constructing femininity and masculinity in John Ruskin’s Sesame and Lilies The article revolves around the question of constructing models of femininity and masculinity in John Ruskin’s lectures.